Tourist of The North Portugal region and local accommodation: influences and motivations - Dieguez, Teresa (2020)
Local Accommodation is increasingly an option for those who travel and seek new concepts or follow trends. The present research aims to understand what the main influence and motivation factors are when the tourist of the north Portugal chooses local accommodation in Portugal and abroad. After a literature review, an online survey was conducted during May and July 2019, with all Portuguese living in the north of Portugal who had travelled at least once over the past 5 years. A random sample of 239 participants was collected and data was treated through SPSS software. The gathered information allowed developing an exploratory descriptive analysis, an inferential analysis and a factor analysis. The results seem to indicate that there is a significant relationship between the national tourist’s adhesions to touristic accommodation in Portugal and abroad. The adhesion to local accommodation in Portugal is not associated with the reasons for the trip/travel, and the adhesion to local accommodation abroad is mostly motivated by leisure. The location (Portugal/abroad) is not relevant to the perception of the national tourist about the touristic accommodation